On Classification of Web Services Using Fuzzy Expert System. Issue 1 (March 2013) - Almulla, Mohammed A.
The evolution of the Internet from static Web pages into dynamic Web services raises a serious challenge of locating desired Web services. One possible way for Web services discovery is to classify Web services into different categories when they are published in a UDDI registry. This paper proposes a knowledge-based solution to the problem through the use of fuzzy expert systems. Our system automatically classifies Web services into specific domains through identifying key concepts/operations inside service textual documentations, and hence builds a lattice of classes of similar Web services. Results obtained by the system are compared with those computed by alternative methods.